A nationwide Danish cohort study challenging the categorisation into right-sided and left-sided colon cancer. Issue 5 (16th May 2013) - Jess, Per; Hansen, Iben Onsberg; Gamborg, Michael; Jess, Tine
Abstract : Objectives: The categorisation of colon cancer (CC) into right-sided (RCC) and left-sided (LCC) disease may not capture more subtle variances in aetiology and prognosis. In a nationwide study, we investigated differences in clinical characteristics and survival of RCC versus LCC and of the complete range of CC subsites. Design: Prospective nationwide cohort study. Setting: The database of the Danish Colorectal Cancer Group (DCCG). Participants: 23 487 CC patients. Outcome measures: Overall survival (Kaplan-Meier plots) and mortality (HR from Cox proportional hazards regression analysis) according to CC localisation. For adjustment and stratification, we used age, sex, ASA score (the American Society of Anaesthesiologists score), tumour location and stage, number of lymph nodes harvested at operation, number of lymph nodes with metastases and presence of distant metastases. Results: Patients with RCC had a higher median age at diagnosis (74.3 years) than patients with LCC (71.8 years; p<0.0001). Overall, the proportion of patients who were women increased the closer the tumour site was to the small intestine. Although RCC patients had higher ASA scores than LCC patients (p<0.0001), the highest ASA scores were observed in patients with cancer in the transverse and descending colon and at both colon flexures. While RCCs overall were more advanced than LCCs (p<0.0001), the most advanced CCs were those of the descending colon, splenic flexure and caecum. RCC mortality was higher than LCC mortality only during the first 2 years (women: HR 1.13; 95% CI 1.06 to 1.20; men: HR 1.27; 95% CI 1.20 to 1.35), and relative to mortality from sigmoid CC, the highest mortality was observed from splenic flexure cancer (HR 1.75; 95% CI 1.54 to 2.00). Conclusions: The present data challenge the simple categorisation of CC into RCC and LCC.